*-wildness of some classes of C^*-algebras - Jushenko, E.; Albeverio, S.; Proskurin, D. P.; Samoilenko, Yu. S. (Methods of Functional Analysis and Topology, 2006)
We consider the complexity of the representation theory of free products of C^*-algebras. Necessary and sufficient conditions for the free product of finite-dimensional C^*-algebras to be *-wild is presented. As a corollary we get criteria for *-wildness of free products of finite groups. It is proved that the free product of a non-commutative nuclear C^*-algebra and the algebra of continuous functions on the one-dimensional sphere is *-wild. This result is applied to estimate the complexity of the representation theory of certain C^*-algebras generated by isometries and partial isometries.